An Investigation of Practices and Tools that Enabled Technology-Mediated Caring in an Online High School - Velasquez, Andrea; Graham, Charles R; West, Richard E (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2013)
The ethic of care has been an important part of the dialogue related to learning in traditional K-12 learning environments particularly because emotional relationships and caring pedagogies have been shown to be particularly important for adolescent learners. However, as online learning has become increasingly popular, there are concerns about the perceived impersonal nature of the online medium, and how this might particularly affect adolescent learners. The purpose of this study was to examine technology choices when experiencing caring interactions in the online schooling context of Mountain Heights Academy (formerly Open High School of Utah). The caring experience of two teacher participants and four of their students was examined through interpretative phenomenological analysis. Results suggest that teacher choices regarding technology use are an integral part of creating caring relationships with students online. The ethics of caring is an essential model in understanding the communication of caring interactions in the online setting.